2016
DOI: 10.1681/asn.2014111138
|View full text |Cite
|
Sign up to set email alerts
|

Differential Ly6C Expression after Renal Ischemia-Reperfusion Identifies Unique Macrophage Populations

Abstract: Macrophages are a heterogeneous cell type implicated in injury, repair, and fibrosis after AKI, but the macrophage population associated with each phase is unclear. In this study, we used a renal bilateral ischemiareperfusion injury mouse model to identify unique monocyte/macrophage populations by differential expression of Ly6C in CD11b + cells and to define the function of these cells in the pathophysiology of disease on the basis of microarray gene signatures and reduction strategies. Macrophage populations… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
66
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 69 publications
(69 citation statements)
references
References 64 publications
3
66
0
Order By: Relevance
“…3C) were profiled, with the cell-surface antigen Ly6C further used as a surrogate to assess myeloid cell activation states (Fig. S1 shows gating (26). A small population of Ly6C low myeloid cells was present in naïve skin, likely made up of dendritic cells and other tissue-resident immune cells (27), whereas few neutrophils, Ly6C hi monocytes, or T cells were found in the uninjured hind paw (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…3C) were profiled, with the cell-surface antigen Ly6C further used as a surrogate to assess myeloid cell activation states (Fig. S1 shows gating (26). A small population of Ly6C low myeloid cells was present in naïve skin, likely made up of dendritic cells and other tissue-resident immune cells (27), whereas few neutrophils, Ly6C hi monocytes, or T cells were found in the uninjured hind paw (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…The CD11b + /Ly6C high population appeared during the acute injury phase, was linked with monocyte/macrophage immune responses, and when depleted led to renoprotection (64), as reported by others (64, 65). The CD11b + /Ly6C intermediate population was present during the repair phase, had a gene signature of wound healing, and when depleted, associated with prolonged renal injury (63). The CD11b + /Ly6C low population had a profibrotic phenotype and dominated during the progressive phase.…”
Section: Pathophysiologymentioning
confidence: 99%
“…Emerging data from human biopsies also corroborate the presence of macrophages in AKI and their persistence in progressive chronic kidney disease; we highlight our current understanding of the mechanisms by which macrophages contribute to injury and repair after AKI. Recent analysis of macrophage populations carefully isolated by differential expressions of Ly6C in CD11b + cells in the kidney injury [31, 32] confirmed that results of previous studies have shown that macrophages (predominantly CD11b + /Ly6C high cells) [30, 31] in the kidney early expressed proinflammatory genes, whereas macrophages within the kidney during the tubular repair phase (CD11b + /Ly6C intermediate cells) expressed more wound-healing markers [30]. It has been proved that decreased MIF concentration in cancer can induce macrophage polarization from proinflammatory macrophages (predominantly CD11b + /Ly6C high cells) to pro-wound healing macrophages (CD11b + /Ly6C intermediate cells) [33].…”
Section: The Role Of Crrt In Inflammation and Metabolic Adaptation Inmentioning
confidence: 99%